Implementation Of Instagram ‘My Rise Clothing Store’ Marketing Strategy Based On Aida Model - Ignatius Bias Galih Prasadhya; Yashinta Putri; Deva Nita Mulya; Aldian Umbu Tamu Ama (Institute of Computer Science (IOCS), 2022)
Digitalization of technology that has been applied in various fields has changed various forms of activities in daily life both in the business environment, government, and social life. Entrepreneurs are also encouraged to change practices in their business in order to survive in the digital era. One way to increase this competitive advantage is to take advantage of social media in running a business. Social Media Marketing and more particularly instagram are becoming increasingly important in consumers’ purchasing decisions,This research aims to analyze My Rise Instagram content with consumer buying interest based on attention, interest, desire, and action (AIDA). This research uses the descriptive qualitative method. The data collection was carried out using observation and in-depth interviews with key informants and informants. Based on the result of research and discussion, the following conclusions can be drawn; First promotional efforts carried out by the My Rise Store through Instagram social media turned out to be effective and had an important role, especially in creating audience awareness about the product. Implementing the AIDA Model through Instagram content has proven to increase traffic visits to an account of Instagram business @yash.uplabel. Second, the owners also pay attention to every piece of content they create based on the AIDA model to make people interested in the product, so finally visit the store and buy the fashion product directly.